2019
DOI: 10.1021/acs.langmuir.9b00689
|View full text |Cite
|
Sign up to set email alerts
|

Surfactant Charge Modulates Structure and Stability of Lipase-Embedded Monolayers at Marine-Relevant Aerosol Surfaces

Abstract: Lipases, as well as other enzymes, are present and active within the sea surface microlayer (SSML). Upon bubble bursting, lipases partition into sea spray aerosol (SSA) along with surface-active molecules such as lipids. Lipases are likely to be embedded in the lipid monolayer at the SSA surface and thus have the potential to influence SSA interfacial structure and chemistry. Elucidating the structure of the lipid monolayer at SSA interfaces and how this structure is altered upon interaction with a protein sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 87 publications
1
17
0
Order By: Relevance
“…Since HMW organic species tends to be surface active, their presence even in relatively small quantities may reduce the equilibrium vapor pressure over drops promoting the activation and growth of cloud droplets (Lohmann et al, 2016;Kubicki et al, 2019). It has been shown that after marine primary aerosol are formed they can become coated with organic surfactants, such as longchain hydrocarbons (Djikaev and Ruckenstein, 2014;Luo et al, 2019). In this study, SML samples were collected in the North Atlantic Ocean to quantify the relative importance of the salt and organic constituents of aerosols emitted from the surface waters.…”
Section: Introductionmentioning
confidence: 99%
“…Since HMW organic species tends to be surface active, their presence even in relatively small quantities may reduce the equilibrium vapor pressure over drops promoting the activation and growth of cloud droplets (Lohmann et al, 2016;Kubicki et al, 2019). It has been shown that after marine primary aerosol are formed they can become coated with organic surfactants, such as longchain hydrocarbons (Djikaev and Ruckenstein, 2014;Luo et al, 2019). In this study, SML samples were collected in the North Atlantic Ocean to quantify the relative importance of the salt and organic constituents of aerosols emitted from the surface waters.…”
Section: Introductionmentioning
confidence: 99%
“…The Infrared Reflection Absorption Spectroscopy (IRRAS) setup has been described previously. 38 , 39 The IR beam from an infrared spectrometer (Bruker Tensor 37) is directed onto the aqueous solution surface in the Petri dish at an angle of 30° from the surface. We chose 30° because that is the optimal angle for the incident beam at an air–water interface for the unpolarized beam used in our setup.…”
Section: Experimental Methods and Materialsmentioning
confidence: 99%
“…3,27 By studying the individual role of each primary subset of algal exudates as demonstrated in the studies above, the fundamental interactions at the ocean's interface and consequent aerosol surfaces can be determined and include interfacial adsorption, 22,27 binding interactions, 28,29 and reaction mechanisms. 30 Biogenic surfactants have also been explored in more complex systems and have been shown to alter surface features, 31 enhance interactions, 24,25,32,33 and influence the overall film properties. 34 Ex situ analysis of the interfacial regime of native marine systems has been reported, with some studies extending to surface tension measurements, 31 Brewster angle microscopy (BAM), 35,36 and sum-frequency generation (SFG) spectroscopy.…”
Section: ■ Introductionmentioning
confidence: 99%